Relationship between intrinsic and extrinsic factors with Erosive Tooth Wear in adults: a cross-sectional study - Valeria RAMIREZ; Adrian LUSSI; María Loreto MARRÓ FREITTE; Pamela VASQUEZ; Vicente ARÁNGUIZ (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The objective of this study was to explore the relationship between intrinsic and extrinsic factors and a high cumulative score of the Basic Erosive Wear Examination (BEWE) in a Chilean adult group. A cross-sectional study was performed with the Ethics Committee's approval from the Universidad de los Andes. A consecutive adult (18 to 46 years old) sampling (n = 553) from the Health Center in San Bernardo-Chile, was selected from September 2016 to January 2017. Dental exams were performed by two trained and calibrated examiners, according to the BEWE index. In order to search for potentially related factors, a hetero-applied questionnaire previously developed and evaluated was applied. Our interest was individuals with severe erosion tooth wear (BEWE ≥ 14). Logistic regression models reporting crude odds ratio (OR) and adjusted OR by age, 95% confidence interval (95%CI), and p-values were estimated. Variables, odds ratios and 95% CI related with BEWE ≥ 14 were: age (OR 1.1 [1.07-1.14]); currently drinking alcohol (OR 1.59 [1.06-2.39]); esophagitis (OR 8.22 [1.60-42.22]); difficulty to swallow (OR 2.45 [1.10-5.44]); chest pain (OR 2.07 [1.18-3.64]); anorexia (OR 3.82 [1.07-13.68]); vitamin C intake (OR 1.92 [1.08-3.43]). Age, alcohol consumption, self-reported esophagitis, history of gastric symptoms, anorexia, and vitamin C intake were related as risk factors to high BEWE scores in this sample of Chilean adults in San Bernardo, Chile.